Links between atherosclerotic and periodontal disease - Chistiakov, Dimitry A.; Orekhov, Alexander N.; Bobryshev, Yuri V. (Experimental and molecular pathology, 2016)
Periodontal disease (PD) and cardiovascular disease (CVD) are highly prevalent in the modern community. Both pathologies are chronic inflammatory disorders, which are influenced by multiple risk factors. In part, these factors such as age, smoking, and diabetes overlap between PD and CVD. Epidemiological studies suggest that PD is strongly associated with increased CVD risk. Biochemical and physiological analyses involving in vitro experiments, animal models, and clinical studies provided evidence for the substantial impact of periodontal pathogens, their virulence factors, and bacterial endotoxins on all general pathogenic CVD mechanisms such as endothelial dysfunction, systemic inflammation, oxidative stress, foam cell formation, lipid accumulation, vascular remodeling, and atherothrombosis. Interventional studies showed moderate beneficial effects of PD treatment on reducing systemic inflammation and endothelial dysfunction. However, no interventional studies were performed to assess whether periodontal therapy can primarily prevent CVD. In summary, current data suggest for a strong contributory role of periodontal infection to CVD but cannot provide sufficient evidence for a role of PD as a cause for cardiovascular pathology.